Household and dietary assessment of women within the reproductive age of 18 to 45 years and adolescents in Vihiga County, Kenya (July 2023) - Maina, Evalyn Waruguru; Aluso, Lillian Olimba; Wanyama, Rosina Nanjala; Termote, Celine; Akingbemisilu, Tosin Harold (2024)
The primary objective of this dataset is to evaluate the socio-economic characteristics, behaviour and dietary intake patterns of women within the reproductive age of 18 to 45 years and adolescents in Vihiga County, Kenya. This data serves as a foundation for understanding nutritional behaviors and informing targeted interventions to improve dietary outcomes in the study population.